Melatonin protects myocardium from ischemia-reperfusion injury in hypertensive rats: Role of myeloperoxidase activity - Sahna, Engin; Deniz, Esra; Bay-Karabulut, Aysun; Burma, Oktay (Taylor & Francis Inc, 2008)
Increased levels of reactive oxygen species, alterations in nitric oxide synthesis, and increased migration of neutrophils to the ischemic tissue play an important role in the pathophysiology of myocardial ischemia-reperfusion (IR) injury. In this study, we have evaluated the effects of melatonin on myeloperoxidase (MPO) activity, tissue glutathione (GSH), lipid peroxidation levels, and blood pressure in L-NAME-induced hypertensive rats with or without IR. NOS inhibitor L-NAME was administrated before inducing cardiac ischemia for 15 days intraperitoneally. For the cardiac ischemia, the left coronary artery was ligated for 30 min, and reperfusion was performed for 120 min after the ischemia. L-NAME treatment in non-ischemic animals increased blood pressure and lipid peroxidation, and decreased glutathione level in myocardial tissue significantly as compared with non-L-NAME-treated animals. Melatonin reversed L-NAME-induced blood pressure elevation and oxidative changes. Cardiac IR increased MDA levels and MPO activity and decreased GSH levels as compared with non-ischemic animals. L-NAME treatment did not change in IR-induced MDA and GSH levels as compared with ischemic control animals. However, MPO activity was significantly higher than control ischemic animals. MDA levels and MPO activity resulting from ischemic injury in melatonin-treated animals were significantly less than L-NAME-treated animals. Taken togetherthe ischemic and non-ischemic control and melatonin-treated animalsthis study shows that neutrophil migration plays an important role on the development of ischemic injury in hypertensive rats.
Keywords: NO; hypertension; melatonin; ischemia-reperfusion; myeloperoxidase; heart